Physical attributes of streetscape in the inner city of Kuala Lumpur: Case study of Bukit Bintang Street and Tun Perak Street / Mohadeseh Mahmoudi Mohadeseh Mahmoudi - Mahmoudi, Mohadeseh (2012)

(untitled)
Physical environment is one of the most influential factors on livability of urban spaces and eventually quality of life of city residents. Recently, the rapid urbanization in Kuala Lumpur city has raised the necessity of examination of the quality and livability of Kuala Lumpur urban spaces. The main aim of this study is to evaluate the quality and livability of Kuala Lumpur streetscapes through examining the physical attributes of studied areas and identifying the physical problems. Bukit Bintang Street and Tun Perak Street which are located in the inner part of Kuala Lumpur City Center were selected as the case studies. To achieve the research objectives, a sequential mixed method was adopted. Firstly, the 15 influential physical attributes on design and livability of streetscape were identified. Secondly, the current conditions of physical attributes of two case study streets examined qualitatively through observation and photography to explore physical problems of the studied areas. Then, questionnaire surveys conducted to examine the importance of identified problems and the role of different organizations on decreasing the problems. The quantitative data were analyzed using SPSS. Correlation was carried to identify the effects of identified physical problems on livability of the areas. The results revealed that some problems such as the traffic congestion, small road, inadequate parking space, improper walkway paving, inadequate planting, lack of renovation of ruined buildings, inadequate facilities for disabled people and inadequate public services and maintenance, mostly deteriorate the livability of the studied streetscapes. In addition, the respondents recognized Kuala Lumpur City Hall as the major responsible organization for improving the problems. Finally, the researcher recommended two groups of strategies - KLCH role and government role - for improvement of the physical quality and livability of Kuala Lumpur city center's streetscapes.